Early alteration of peripheral blood lymphocyte subsets as a risk factor for delirium in critically ill patients after cardiac surgery: A prospective observational study - Li, Xiao; Cheng, Wei; Zhang, Jiahui; Li, Dongkai; Wang, Fei; Cui, Na (Frontiers in Aging Neuroscience, 2022)
Objective: There is a high incidence of delirium among patients with organ dysfunction undergoing cardiac surgery who need critical care. This study aimed to explore the risk factors for delirium in critically ill patients undergoing cardiac surgery and the predictive value of related risk factors. Methods: We conducted a prospective observational study on adult critically ill patients who underwent cardiac surgery between January 2019 and August 2021. Patients were consecutively assigned to delirium and non-delirium groups. Univariate analysis and multivariate logistic analysis were used to determine the risk factors for delirium. Receiver operating characteristic curves and a nomogram were used to identify the predictive value of related risk factors. Results: Delirium developed in 242 of 379 (63.9%) participants. Acute Physiology and Chronic Health Evaluation II (APACHE II) and Sequential Organ Failure Assessment (SOFA) scores were 14.2 ± 5.6 and 18 ± 8.4, respectively. Patients with delirium had longer cardiopulmonary bypass time (149.6 ± 59.1 vs 126.7 ± 48.5 min, p < 0.001) and aortic cross-clamp time (98.7 ± 51.5 vs 86.1 ± 41.6 min, p = 0.010) compared with the non-delirium group. The area under the curve was 0.824 for CD4+ T cell count and 0.862 for CD4/CD8 ratio. Multivariate analysis demonstrated that age [odds ratio (OR) 1.030, p = 0.038], duration of physical restraint (OR 1.030, p < 0.001), interleukin-6 (OR 1.001, p = 0.025), CD19+ B cell count (OR 0.996, p = 0.016), CD4+ T cell count (OR 1.005, p < 0.001) and CD4/CD8 ratio (OR 5.314, p < 0.001) were independent risk factors for delirium. A nomogram revealed that age, cardiopulmonary bypass duration, CD4+ T cell count and CD4/CD8 ratio were independent predictors of delirium. Conclusions: Age, duration of physical restraint, CD4+ T cell count and CD4/CD8 ratio were reliable factors for predicting delirium in critically ill patients after cardiac surgery. The receiver operating characteristic curves and nomogram suggested a potential role for CD4+ T cells in mediating potential neuroinflammation of delirium.